The Impact of Using a Translanguaging Strategy Assisted by the DingTalk Platform on Students' Academic Writing Skills - Herlina Lindaria Simanjuntak (Jurnal Pendidikan Bahasa Inggris Undiksha, 2026)
One of the obstacles in learning to write in English is adjusting the linguistic knowledge of the first language to English, so an appropriate strategy is needed. The purpose of this study was to investigate the impact of a translanguaging strategy assisted by the DingTalk platform on the students' academic writing skills. This research was based in a multilingual context, utilizing students' linguistic scaffolding in a virtual environment. This mixed methods study combined quasi-experimental and qualitative investigations involving 200 university students. Participants were divided into two groups: The experimental group received DingTalk platform-assisted translanguaging strategy intervention, while the control group received traditional teaching. The instruments used were an english language competency test, an academic writing composition assessment rubric, interview questions, and the DingTalk platform. Data analysis used descriptive analysis, independent sample t-tests, and ANOVA. The research findings indicate that the DingTalk platform-assisted translanguaging strategy improved academic writing skills (content, organization, vocabulary usage, grammar, and mechanics). In addition, the intervention also created positive perceptions in cognitive and affective aspects during the process of learning english as a second language. This improvement occurred because the translanguaging strategy facilitated students' optimization of linguistic knowledge from their first language, Indonesian, and adaptation to English grammar. Furthermore, DingTalk platform features also contributed to the quality of students' academic writing, such as immersive features, feedback, autocorrect, and discussions that corrected errors, thus improving students' academic writing skills. This study implies that the integration of pedagogy and technology can improve writing skills in second language learning.